2011
DOI: 10.1620/tjem.224.87
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Vein Thrombosis Is Associated with Large Uterine Fibroids

Abstract: Pulmonary thromboembolism (PE) may occur upon a patient's first postoperative attempt of ambulation. PE is a serious complication, often leading to shock or sudden death. Reported rates of PE following gynecologic surgery are between 0.3% and 0.8%, while the incidence of postoperative deep-vein thrombosis (DVT), the major cause of PE, is between 17% and 20%. Therefore, effective preventive measures, such as preoperative assesment for asymptomatic DVT, should be considered. It is well known that DVT and/or PE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Some malignancies are known to increase coaguability, and DVT/ PE has been reported in patients with ovarian cancer (Suzuki et al 2010). An increased risk of DVT has also been demonstrated in patients with large uterine fibroids, possibly due to compression of adjacent blood vessels including the inferior vena cava (Shiota et al 2011). Suzuki et al (2010) have reported an incidence rate of 3.17% for perioperative DVT in women with surgical gynecological disease, including patients with malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some malignancies are known to increase coaguability, and DVT/ PE has been reported in patients with ovarian cancer (Suzuki et al 2010). An increased risk of DVT has also been demonstrated in patients with large uterine fibroids, possibly due to compression of adjacent blood vessels including the inferior vena cava (Shiota et al 2011). Suzuki et al (2010) have reported an incidence rate of 3.17% for perioperative DVT in women with surgical gynecological disease, including patients with malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al (2010) have reported an incidence rate of 3.17% for perioperative DVT in women with surgical gynecological disease, including patients with malignant tumors. In patients with benign gynecologic diseases, such as uterine fibroids, the size of the mass has been found to be a factor for increased risk of DVT (Shiota et al 2011). If these large masses compress the inferior vena cava and other pelvic veins, the resulting venous stasis may lead to DVT (Shiota et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An association of a deep vein thrombosis with a uterine myoma has been previously described [4,5], but few patients presented extensive thrombosis [6,7].…”
Section: Introductionmentioning
confidence: 96%